The 'in vivo lifestyle' of bile acid 7α-dehydroxylating bacteria: comparative genomics, metatranscriptomic, and bile acid metabolomics analysis of a defined microbial community in gnotobiotic mice. (3rd May 2020) - Ridlon, Jason M.; Devendran, Saravanan; Alves, João Mp; Doden, Heidi; Wolf, Patricia G.; Pereira, Gabriel V.; Ly, Lindsey; Volland, Alyssa; Takei, Hajime; Nittono, Hiroshi; Murai, Tsuyoshi; Kurosawa, Takao; et al.
ABSTRACT: The formation of secondary bile acids by gut microbes is a current topic of considerable biomedical interest. However, a detailed understanding of the biology of anaerobic bacteria in the genus Clostridium that are capable of generating secondary bile acids is lacking. We therefore sought to determine the transcriptional responses of two prominent secondary bile acid producing bacteria, Clostridium hylemonae and Clostridium hiranonis to bile salts ( in vitro ) and the cecal environment of gnotobiotic mice. The genomes of C. hylemonae DSM 15053 and C. hiranonis DSM 13275 were closed, and found to encode 3, 647 genes (3, 584 protein-coding) and 2, 363 predicted genes (of which 2, 239 are protein-coding), respectively, and 1, 035 orthologs were shared between C. hylemonae and C. hiranonis . RNA-Seq analysis was performed in growth medium alone, and in the presence of cholic acid (CA) and deoxycholic acid (DCA). Growth with CA resulted in differential expression (>0.58 log2 FC; FDR < 0.05) of 197 genes in C. hiranonis and 118 genes in C. hylemonae . The bile acid-inducible operons ( bai ) from each organism were highly upregulated in the presence of CA but not DCA. We then colonized germ-free mice with human gut bacterial isolates capable of metabolizing taurine-conjugated bile acids. This consortium included bile salt hydrolase-expressing Bacteroides uniformis ATCC 8492, Bacteroides vulgatus ATCC 8482, Parabacteroides distasonis DSM 20701, as well as taurine-respiring Bilophila wadsworthia DSM 11045, and deoxycholic/lithocholic acid generating Clostridium hylemonae DSM 15053 and Clostridium hiranonis DSM 13275. Butyrate and iso-bile acid-forming Blautia producta ATCC 27340 was also included. The Bacteroidetes made up 84.71% of 16S rDNA cecal reads, B. wadsworthia, constituted 14.7%, and the clostridia made up <.75% of 16S rDNA cecal reads. Bile acid metabolomics of the cecum, serum, and liver indicate that the synthetic community were capable of functional bile salt deconjugation, oxidation/isomerization, and 7α-dehydroxylation of bile acids. Cecal metatranscriptome analysis revealed expression of genes involved in metabolism of taurine-conjugated bile acids. The in vivo transcriptomes of C. hylemonae and C. hiranonis suggest fermentation of simple sugars and utilization of amino acids glycine and proline as electron acceptors. Genes predicted to be involved in trimethylamine (TMA) formation were also expressed.